1989
DOI: 10.1172/jci113962
|View full text |Cite
|
Sign up to set email alerts
|

A live avirulent mutant Legionella pneumophila vaccine induces protective immunity against lethal aerosol challenge.

Abstract: IntroductionWe have examined the capacity of a live avirulent mutant form of the intracellular bacterial pathogen Legionella pneumophila to induce immune responses and protective immunity in guinea pigs. The mutant L. pneumophila is nonlethal to guinea pigs and does not revert to virulence with passage through guinea pigs. In contrast, exposure of guinea pigs to aerosols containing wild-type L. pneumophila induces a pneumonic illness that clinically and pathologically resembles Legionnaires' disease in humans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…Male Hartley strain guinea pigs weighing 250-300 g (Simonson Laboratories, Gilroy, CA), were cared for as previously described ( 18). They were observed in the vivarium for 1 wk before challenge with L. pneumophila to ensure that they were healthy.…”
Section: Methodsmentioning
confidence: 99%
“…Male Hartley strain guinea pigs weighing 250-300 g (Simonson Laboratories, Gilroy, CA), were cared for as previously described ( 18). They were observed in the vivarium for 1 wk before challenge with L. pneumophila to ensure that they were healthy.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies from this laboratory have demonstrated that guinea pigs immunized with a sublethal aerosolized dose of wild-type L. pneumophila, or with an aerosolized dose of an avirulent mutant L. pneumophila develop humoral and cellmediated immune responses to wild-type L. pneumophila antigens, and protective immunity against lethal aerosol challenge with wild-type L. pneumophila (15,16). To identify immunoprotective antigens of L. pneumophila, we have focused our attention on native antigens recognized by the lymphocytes of such immune guinea pigs.…”
Section: Introductionmentioning
confidence: 99%
“…To identify immunoprotective antigens of L. pneumophila, we have focused our attention on native antigens recognized by the lymphocytes of such immune guinea pigs. Previous studies have identified two such antigenic preparations: the major secretory protein (MSP)1 of L. pneumophila and L. pneumophila membranes (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…L'antigène détecté est un composant du LPS de la paroi cellulaire de L. pneumophila. En moyenne, la valeur prédictive positive des version [27], mais également par le succès des vaccinations dans des modèles animaux [28]. Il y a production de lymphocytes B mémoires et d'anticorps dont le rôle protecteur a été démontré au cours des réin-fections [29].…”
Section: La Recherche D'antigènes Solubles Dans Les Urinesunclassified